Evaluation of efficiency and pressure parameters of water supply systems for fire protection purposes in the light of hydrant tests - Piórek, Daniel; Stańczyk, Justyna; Licznar, Paweł (Instal, 2022)
Testing the performance of hydrants and carrying out their annual inspection are the activities aimed at fulfilling the function of water supply system in the context of fire-fighting water supply to settlement units. The duty of checking the condition of their work rests on the owners of firewater supply network and despite the fact that national regulations contain information about requirements for water supply system as a source of water for fire extinguishing, there are still some methodically unregulated issues, e.g. the procedure of carrying out hydrant tests. Water consumed for own purposes of the waterworks, among other things during the hydrant tests, is in the water balance so called unbilled authorized consumption. The article presents the results of the research on the hydrant tests carried out in the water supply system in Olesnica and the analysis of the annual volume of water consumed during these activities. The evaluation of efficiency and pressure of water flowing out of hydrants was done in the light of reviewing national and foreign recommendations and requirements concerning their testing.
Keywords: water supply networks; hydrant testing; hydrant efficiency; fire protection requirements